REKONTRUKSI SENI TRADISI BUMBUNG GEBYOG UNTUK MENUNJANG DESA WISATA PINGE KECAMATAN MARGA KABUPATEN TABANAN - I.M. mega; N.L.R. Purnawan; N.W. Suartini (Buletin Udayana Mengabdi, 2018)
Community service activities aims to reproduce the traditional dance "Bumbung Gebyog " into a peformancefor tourists in the village tourism Pinge, District of Marga, Kabupaten Tabanan. The method applied incommunity service are as follows: (1) coordination and participatory communication with indigenousvillages / manager of a tourist village Pinge to formulate a program from the planning, operational andevaluation; (2) gather information about the dance "bumbung gebyog" of the parties involved in the arts inthe past gebyog tube; (3) construction of dance movements and choreography performances gebyog tube; (4)Assistance is meeting regularly and sustainably among companion with target communities to science andtechnology transferred can be carried out independently by the community. The results obtained showed thatthe reconstruction activities bumbung dance gebyog already shooting went well marked by the mastery of thedancers and gamelan players were pretty good. After the 9 (nine) meetings throughout the dancers have beenable to practice dance moves independently. Similarly, the skills gambelan players, all musicians have beenable to play a dance tone drilled in accordance with their respective instruments. Dance tube gebyog result ofreconstruction has been staged at the Tourism Village louncing which was attended by Minister of StateOwned Enterprises (SOEs).